LC3-Mediated Mitophagy After CCCP or Vibrio splendidus Exposure in the Pacific Oyster Crassostrea gigas - Sun, Jiejie; Lv, Xiaoqian; Leng, Jinyuan; Wang, Lingling; Song, Linsheng (Frontiers in Cell and Developmental Biology, 2022)
Mitochondrial selective autophagy, known as mitophagy, surveils mitochondrial population by eliminating superfluous and/or impaired organelles to mediate cellular survival and viability in response to injury/trauma and infection. In this study, the components of mitophagy pathway in the Pacific oyster Crassostrea gigas were screened from NCBI with reference to the protein sequences of human mitophagy process. A total of ten mitophagy process related genes were identified from C. gigas, including NIX, FUNDC1, PHB2, Cardiolipin, P62, VDAC2, MFN2, PARL, MPP, and OPTN. They shared high similarities with their homologues in human mitophagy pathway and were expressed in various tissues of C. gigas. After CCCP exposure, the fluorescence intensity of mitochondrial probe JC-1 monomers increased significantly in haemocytes, while the fluorescence intensity of JC-1 aggregates decreased significantly. Meanwhile, the fluorescence of lysosomes was found to be co-localized with that of CgLC3 and mitochondria in CCCP-treatment haemocytes. Double- and single-membrane-bound vacuoles resembling autophagic structures were observed in the haemocytes after CCCP exposure. The fluorescence intensity of JC-1 monomers and the abundance of CgLC3Ⅱ in haemocytes both increased after Vibrio splendidus exposure. At the same time, the green signals of CgLC3 were co-localized with red signals of mitochondria and the fluorescence intensity of autophagy increased significantly in haemocytes after V. splendidus exposure. The results confirmed the existence of complete mitophagy pathway in molluscs for the first time, which was helpful for further studying on the function of mitochondrial autophagy in molluscs.